An??lise dos valores pessoais e a influ??ncia no desempenho de vendas dos corretores de im??veis - Gines J??nior, Clovis Soler (2015)
This work aims to verify the influence of the hierarchy of personal values in the sales performance of Realtors from the city of S??o Paulo. To this end, part of a rescue of the literature on the determinants of the performance of sales and the main constructs analyzed by researchers, noting the importance devoted to psychological factors. Using a quantitative research of descriptive nature and the withdrawal method, 169 collected questionnaires for the personal and professional profile analysis for realization of a longitudinal study. Regarding the second part of the survey, 143 forms were collected with the instrument C-VAT (Culture and Value Analysis Tool), developed by Nelson (2003), for the cross-sectional study. The results pointed to the growth in the number of professionals working in the sector, for the high level of satisfaction with the profession, the dimension of C-VAT is related to job performance; personal relationships and thought are related to poor performance; the dimension control is a category with common averages for the three groups performance; the highest average was for thought, for brokers with low performance; and, the lowest average was for brokers with superior performance in the category of personal relationships. Finally, Realtor profile with differentiated performance involves effort, quality, planning and flexibility.